Competency Education Implementation: Examining the Influence of Contextual Forces in Three New Hampshire Secondary Schools - Aubrey Scheopner Torres; Jessica Brett; Joshua Cox; Sara Greller (SAGE Publishing, 2018)
Competency education, a K-12 reform aimed to ensure that all students meet high expectations, requires that students demonstrate mastery of competencies to advance and earn credit, typically through assessments where students apply knowledge. Students receive more time and possibly personalized instruction to demonstrate mastery if needed. Competency education demands changes to traditional practices, including scheduling and grading. This qualitative case study describes how three districts in New Hampshire implemented this reform in secondary schools. Findings reveal that despite over 6 years of progress at each site, the reform had not been fully implemented due to inertial, technical, normative, and political challenges. Changes to grading and assessment were particularly difficult to implement.